Nurturing spirituality in secular classrooms - Fraser, Deborah (International journal of children's spirituality, 2004)
Since 1999 the New Zealand secular school curriculum has included a statement on fostering children's spirituality in classrooms. This statement defines spirituality in a broad fashion and includes reference to Maori (indigenous New Zealander) views on spirituality. The implications of this for classroom teachers have not been researched in this country and therefore this paper reports on a study that examined teachers' views on spirituality and the implications for the children they teach. The methodology focused on the experiences of nine teachers in two multicultural secular primary schools. The classroom experiences of a spiritual nature that the teachers recounted, while many and varied, revealed some common themes that related to the climate of the classrooms. Such classrooms were characterized as being non-judgemental and non-self-conscious and as places where a community of spiritual discourse was encouraged and where deeply meaningful activities and events occurred. The findings suggest that while teachers cannot plan and predict precisely what will foster spirituality in classrooms, teachers can cultivate a climate that enhances children's spirituality.